Dental caries and gingival health condition among secondary school adolescents in relation to the nutritional status in Kerbala City, Iraq - Kareem, Ahmed R.; Alwaheb, Athraa M.; Abdulhameed, Nader F. (Journal of Baghdad College of Dentistry, 2024)
Background: Oral health as a part of general health is affected by various, factors including oral hygiene, smoking, age, nutritional status, and socioeconomic status. This study aims to measure the impact of nutritional status on the prevalence and severity of some oral health variables (dental caries and gingival health conditions) to develop plans for future reduction and prevention of both diseases. Materials and methods: The sample included a total of 500 male students aged 15 years old who were randomly selected from secondary schools in Karbala City, Iraq. Dental caries, and gingival health condition were recorded. Anthropometric measurements include measurement of weight and height to determine the BMI =Body weight / (height)2 = BMI kg/m2 and using the CDC growth chart to determine the nutritional status. Data analysis were done by using one-way analysis of variance and Games-Howell post hoc test. Results: The prevalence of dental caries was (95.60%). Caries (DS) and missing teeth (MS) are more prevalent in the underweight group, whereas filling (FS) is more prevalent in the normal-weight group. Caries-free percentages were higher in the group of risk of overweight (6.82%) compared with other nutritional groups. Meanwhile, the prevalence of gingivitis among the students was 100%, all students have had the moderate type of gingivitis (1.1–2). The highest mean of gingivitis belonged to the normal weight group (1.923) and there was a significant difference observed. Conclusion: In this study, dental caries experience was not significantly affected by nutritional status. Meanwhile, nutritional status had a significant impact on the gingival health condition which attracted attention to the importance of healthy nutrition concerning oral health and to develop of a good nutritional school program.